Pengaruh Intensitas Cahaya Terhadap Laju Fotosintesis pada Tanaman Bayam (Amaranthus Sp.) - Adelia Saputri; Muhammad Suwignyo Prayogo; Faiqotun Ni’mah (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
Photosynthesis is a vital process for plants in converting light energy into chemical energy stored in organic compounds. Light intensity is one of the main factors influencing the efficiency of this process. This study aims to determine the effect of different light intensities on the photosynthesis rate and growth of spinach plants (Amaranthus sp.), which is a C4 plant species.The method used was a quantitative experiment with three light intensity treatments: low (0–10 lux), medium (10–20 lux), and high (>20 lux), each replicated three times over six weeks. Observed parameters included plant height, number and length of leaves, as well as the photosynthesis rate measured using the IRGA method.The results showed that light intensity significantly affected the growth and photosynthesis rate of spinach plants. The high light treatment produced the most optimal growth, with an average plant height of 4.92 ± 0.4 cm and the highest photosynthetic activity. Conversely, the low light treatment caused symptoms of etiolation, reduced vitality, and faster plant death, averaging by the third week.In conclusion, increasing light intensity significantly enhances photosynthesis efficiency and growth in spinach plants. These results can serve as a basis for regulating light intensity in cultivation systems, both conventional and hydroponic.